School's cool lickety split - Williams, Harland 1962- (Canada : Durkin Haves, 1993)
A young dinosaur has second thoughts about the first day of school until he finds out how it's cool. A rhyming tale
Primary
Keywords: Stories in rhyme; Dinosaurs -- Fiction; Self-acceptance -- Fiction